Lessons from individualized cryoballoon sizing. Is there a role for the small balloon?. Issue 4 (October 2017) - Hartl, Stefan; Dorwarth, Uwe; Bunz, Benedikt; Wankerl, Michael; Ebersberger, Ullrich; Hoffmann, Ellen; Straube, Florian
Abstract: Background: Cryoablation for paroxysmal atrial fibrillation (PAF) is well established. The single-big-balloon strategy has been preferred for pulmonary vein isolation (PVI) using the second generation cryoballoon (CBG2). Individual PV-morphologies raise the question if an individualized anatomic approach using the 23-mm or 28-mm CB is reasonable. Methods: Consecutive patients were prospectively enrolled in the non-randomized single-center study. Patients were treated with the 28-mm CB, if any PV was >21 mm, the 23-mm CB, if all PV were ≤21 mm, or both sizes, if PVI was difficult. The primary endpoint was arrhythmia-free survival. The secondary endpoint considered procedural results and complications. Results: Overall, 197 patients with symptomatic PAF (64 ± 11 years, 36% female) were included. Acute PVI was achieved in 99.9% of PV. Based on preprocedural imaging, the 28-mm CB was applied as the primary catheter in 47% (92/197 patients), the 23-mm CB in 53% (105/197, p  = 0.23). The 23-mm CB group included more females, patients with short left atrial (LA)-diameters (each p  < 0.01), and smaller patients ( p  = 0.04). Both CB-sizes were used in 24% (47/197). Additional 23-mm CB usage was necessary in 23% (21/92) of patients, mainly because of insufficient PV-occlusion with the 28-mm CB. Additional 28-mm CB usage was necessary in 25% (26/105, p  = 0.82), mainly because PV diameters were larger than initially measured. Both CB-sizes were equally safe and effective with a low complication rate and an overall success rate of 86% at 12 and 71% at 18 months (6% on antiarrhythmic drugs). No predictors for AF-recurrence were identified. Conclusion: CB ablation can sometimes be challenging. The 28-mm CB is the preferred catheter in all patients. If balloon positioning is difficult, the 23-mm CB is an option to achieve PVI in small veins. Further studies need to investigate if the 23-mm CB could be beneficial as the primary CB in females with small body height and short LA diameter.